Identification of poisonous plants and their solutions for traditional livestock in Bojonegoro District, East Java, Indonesia - Pratama, Anggi Muhtar; Herawati, Okti; Nuranisa, Nuri Rahma; Hanifah, Nurul; Wijayanti, Agustina Dwi; Rahmatullah, Satyaguna; Nuraini, Elfia; Budiyanto, Agung (Society for Indonesian Biodiversity, 2022)
Local farmers in Bojonegoro District use plants as the main food source and to treat several diseases for their livestock. However, they also comprise a large variety of poisonous plants known by a secondary chemical compound that causes death in the livestock. This study aims to identify the potentially poisonous plants to livestock and their veterinary importance. The study was conducted by interviewing local farmers as we require data as a source of information to provide an overview of their knowledge and experience about poisonous plants that can endanger livestock health. Respondents consisted of 40 local farmers from more than 20 livestock groups in Bojonegoro District. Data were analyzed by Frequency of Citation (Fic), Relative Frequency of Citation (RFC), Frequency of Plant Part (FPP), Symptoms of Poisonous Plants Frequency (SPPF), Livestock Affected Frequency (LAF). A total of nine plants were identified and documented to have poisonous effects on livestock animals, namely leaf of lophatheri (Lophatherum gracile), leaf and tuber skin of cassava (Manihot esculenta), leaf of jack bean (Canavalia ensiformis), leaf of sorghum (Sorghum bicolor), leaf of Chinese albizia (Albizia chinensis), leaf of sweet potato (Ipomoea batatas), leaf of peanut (Arachis hypogaea), rotten fruit of (jackfruit Artocarpus heterophyllus), and leaf of winged bean (Psophocarpus tetragonolobus). Leaf of Lophatherum gracile was the most poisonous plant part for livestock. Furthermore, the leaves of plants are frequently poisonous. Bloating, hypersalivation, frothy mouth, death, and inappetence were among the frequently manifested signs by poisoned livestock. Moreover, this study showed that ruminants species were the most susceptible to poisoned animals. Improper handling of plants for animal feed is thought to trigger poisoning. Therefore a proper feeding preparation is needed before being given as forage. Although those plants can cause toxic effects on livestock, they have tremendous potential to become herbal medicine with the proper formulation.